Teacher’s Belief in Enhancing Children Imagination Through Children Malay Traditional Song - Ariffin, Azli; Saedah Siraj; Abdul Talib bin Mohamed Hashim (European Journal of Social Science Education and Research, 2016)
The purpose of this study is to examine the teacher’s beliefs on imagination construction of preschool children in class, explore and understand the beliefs of preschool teachers on the concept of imagination and understand the beliefs of teachers on using children traditional Malay songs to improve preschool children's imagination. This exploratory study adopted the use of qualitative method of inquiry to provide an in-depth understanding of the area being investigated. Interview and observation of four preschool teachers were purposively selected from two government schools were used to collected data. Findings revealed that all the teachers in this study expressed their views that All the teachers involved in this study expressed their views that imagination is related to creativity and it is regarded as fundamental to the child's ability to be creative. All the teachers also believe that children traditional Malay songs can boost the child's imagination because such songs have the characteristics that suit well with children. Hence the songs are easy to be appreciated and understood by the children and indirectly it can simplify the process of building child's imagination.
Keywords: Imaginations, creativity, beliefs